Treatment of produced water originated from oil and gas production wells: a pilot study and cost analysis - Ersahin, Mustafa Evren; Ozgun, Hale; Kaya, Recep; Kose Mutlu, Borte; Kinaci, Cumali; Koyuncu, Ismail (Springer Science and Business Media LLC, 2017)
Produced water originated from oil and gas production wells was treated by a pilot-scale system including pre-treatment (chemical precipitation), pre-filtration, and post-filtration units. Pre-filtration unit consisted of sand filter, granulated activated carbon (GAC) filter, and ultrafiltration (UF) membrane. Post-filtration unit included reverse osmosis (RO) membrane unit. In this study, two different RO membranes including sea water (SW) and brackish water (BW) membranes were comparatively evaluated in terms of treatment and filtration performance. Besides, a cost analysis was conducted for a real scale RO membrane unit by using the data obtained from the pilot plant study. Average fluxes of 12.7 and 9.4 L/m2 h were obtained by SW and BW membrane units, respectively. Higher COD and conductivity removal efficiencies were obtained by SW membrane in comparison to BW membrane. Total cost of 0.88 €/m3 was estimated for a RO plant treating produced water with a flowrate capacity of 300 m3/d.
Keywords: Osmosis; Ultrafiltration; Membranes, Artificial; Pilot Projects; Wastewater; Water Purification; Charcoal; Costs and Cost Analysis; Chemical Precipitation; Oil and Gas Fields; Filtration